P18.03.B Long term effects of therapeutic embolization of radiographically suspected meningiomas regarding tumour- and necrosis volume as well as patients' symptoms. (5th September 2022) - Pedersen, M; Eibl, T; Nania, A; Voit-Höhne, H; Schrey, M; Steiner, H; Holtmannspötter, M
Abstract: Background: Preoperative embolization of radiographically suspected intracranial meningiomas is performed to reduce intraoperative blood loss and to facilitate resection. However, there is paucity of evidence examining the effect of embolization as a sole intervention on the tumor volume and the patient's neurocognitive symptoms. The objective of this study was to investigates the influence of therapeutic embolization on tumor- and necrosis volume and neurocognitive symptoms in absence of surgical intervention. Material and Methods: Between January 2019 and June 2021, 4 patients (median age 82, 1 female) with 5 radiographically suspected intracranial meningiomas, underwent endovascular embolization with liquid embolizate and coils, without subsequent surgery. Indication for embolization was history of previous multiple surgery contraindicating further surgical intervention or patients will. Neurological status (on admission, discharge from hospital and 5 months after embolization), medical history, medication, MRI (location, tumor- and necrosis volume, development of edema, complications), DSA (extent of embolization, arterial supply) and procedural complications were recorded. In 3 patients with 4 tumors, an MRI scan was performed. The calculation of tumor- and necrosis volume was done manually with a semiautomatic segmentation tool. One patient with one tumor received CT scans due to a cardiac pacemaker and was therefore excluded from volumetric analysis. Results: The average tumor volume was 44, 83 ± 13, 82 cm3 on admission, 45, 33 ± 16, 3 cm3 5 days after embolization (+1%) and 39, 93 ± 29, 39 cm3 (-11%) after 5 months. The average necrosis diameter was 41, 76 ± 9, 33 mm after 5 days and 6, 05 ± 6, 43 mm after 5 months. The perifocal oedema decreased in 2/3 Patients. Tumor blood supply was via 2, 4 ± 1, 34 vessels, 1, 2 ± 0, 45 vessels were embolised. On admission, 3 patients showed neurocognitive symptoms. At discharge and in the follow-up, in 2 patients the symptoms had improved, one patient experienced a complete symptom regression. In one patient the embolization was complicated by dissection of the middle meningeal artery. The same patients perifocal oedema increased in the further clinical course with accompanying deterioration of the pre-existing hemiparesis from moderate to severe. Supported with dexamethasone medication, the oedema and symptoms declined to a mild residual paresis. None of the patients developed a long-term neurocognitive deficit related to embolization. Conclusion: Therapeutic endovascular embolization of radiographically suspected intracranial meningiomas reduced the tumor volume and led to long-term improvement of pre-existing neurocognitive symptoms. In the future, these effects should be verified in larger studies.